Insights into the Drought and Heat Avoidance Mechanism in Summer-Dormant Mediterranean Tall Fescue - Missaoui, Ali M.; Malinowski, Dariusz P.; Pinchak, William E.; Kigel, Jaime (Frontiers in Plant Science, 2017)
Summer dormancy is an evolutionary response that some perennial grasses adopted as an avoidance strategy to escape summer drought and heat. It is correlated with superior survival after severe summer droughts in many perennial grass species originating from Mediterranean environments. Understanding the genetic mechanism and environmental determinants of summer dormancy is important for interpreting the evolutionary history of seasonal dormancy and for the development of genomic tools to improve the efficiency of genetic selection for this important trait. The objectives of this research are to assess morphological and biochemical attributes that seem to be specific for the characterization of summer dormancy in tall fescue, and to validate the hypothesis that genes underlying stem determinacy might be involved in the mechanism of summer dormancy. Our results suggest that vernalization is an important requirement in the onset of summer dormancy in tall fescue. Non-vernalized tall fescue plants do not exhibit summer dormancy as vernalized plants do and behave more like summer-active types. This is manifested by continuation of shoot growth and high root activity in water uptake during summer months. Therefore, summer dormancy in tall fescue should be tested only in plants that underwent vernalization and are not subjected to water deficit during summer months. Total phenolic concentration in tiller bases (antioxidants) does not seem to be related to vernalization. It is most likely an environmental response to protect meristems from oxidative stress. Sequence analysis of the TFL1 homolog CEN gene from tall fescue genotypes belonging to summer dormant and summer active tall fescue types showed a unique deletion of three nucleotides specific to the dormant genotypes. Higher tiller bud numbers in dormant plants that were not allowed to flower and complete the reproductive cycle, confirmed that stem determinacy is a major component in the mechanism of summer dormancy. The number of variables identified in these studies as potential players in summer dormancy in tall fescue including vernalization, TFL1/CEN, water status, and protection from oxidative stress are a further confirmation that summer dormancy is a quantitative trait controlled by several genes with varying effects and prone to genotype by environment interactions.